Targeting and the impacts of India's MGNREGS - Liu, Yanyan; Barrett, Christopher B.; Chau, Nancy H.; Das, Upasak; Deininger, Klaus; Gustafson, Sara; Narayanan, Sudha; Sheahan, Megan; Soundararajan, Vidhya (International Food Policy Research Institute, 2020)
MGNREGS has shown striking heterogeneity in pro-poor targeting across states. The declining demand for MGNREGS in recent years is due mainly to local imple-mentation failures that discourage workers. In Andhra Pradesh, MGNREGS significantly improved the welfare of participating households, especially the poor, scheduled castes and tribes, and casual laborers. It is desirable to provide MGNREGS work during the agricultural lean seasons - when work opportunities are scarce - rather than the peak seasons.